Azithromycin Versus Ofloxacin in Treatment of Enteric Fever in Children - Ammara Manzoor, Tariq Mahmood, Rubina Zulfiqar (Journal of Rawalpindi Medical College, 2014)
Background: To compare the clinical efficacy of Azithromycin versus Ofloxacin in the treatment of typhoid fever in terms of the proportion of children becoming afebrile on 5th day of treatment. Methods: In this randomized controlled trail 230 patients of Typhoid fever, age ranging from 2-12 years, were included. One hundred and fifteen patients were given Azithromycin and 115 patients were given Ofloxacin randomly. Patients were randomly divided into two groups . Group A was given Azithromycin 10 mg/kg/day once daily orally for 7 days.Group B was given Ofloxacin 15mg/kg/day in two divided doses orally for 7 days. Both the groups were observed for duration of becoming afebrile on 5th day of treatment. Investigation to be done during hospital stay was Typhidot (IgM antibodies) . Chi-square test was used to compare efficacy (afebrile on day 5) of both drugs.P-value < 0.05 was considered significant. Results: The age range was from 5 to 12 years with a mean age of 7.7 ±2.45. 125 (54.3 %) were males and 105 (45.7 %) were females. 59.1% patients became afebrile on 5th day of treatment while 40.9 % patients failed to become afebrile.In the Azithromycin group 69.6 % patients became afebrile on day 5th . In the Ofloxacin group, 48.7% became afebrile on day 5th . Proportion of patients becoming afebrile on 5th day of treatment was significantly higher in the azithromycin group as compared to Ofloxacin group (p= 0.01) Conclusion: Azithromycin is more effective in children with typhoid fever in terms of greater proportion of children becoming afebrile on day 5th of treatment